2016
DOI: 10.15252/msb.20156423
|View full text |Cite
|
Sign up to set email alerts
|

Differential dynamics of the mammalian mRNA and protein expression response to misfolding stress

Abstract: The relative importance of regulation at the mRNA versus protein level is subject to ongoing debate. To address this question in a dynamic system, we mapped proteomic and transcriptomic changes in mammalian cells responding to stress induced by dithiothreitol over 30 h. Specifically, we estimated the kinetic parameters for the synthesis and degradation of RNA and proteins, and deconvoluted the response patterns into common and unique to each regulatory level using a new statistical tool. Overall, the two regul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
138
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(172 citation statements)
references
References 67 publications
20
138
1
1
Order By: Relevance
“…The expression of functional proteins is tightly regulated at the post-transcriptional level, including translational regulation and post-translational modification (Cheng et al 2016;Liu and Aebersold 2016;Peng et al 2015;Vogel and Marcotte 2012). Likewise, our comparative 2DE analysis showed that post-transcriptional regulation has a large impact on the expression of functional proteins during xylem vessel cell differentiation.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The expression of functional proteins is tightly regulated at the post-transcriptional level, including translational regulation and post-translational modification (Cheng et al 2016;Liu and Aebersold 2016;Peng et al 2015;Vogel and Marcotte 2012). Likewise, our comparative 2DE analysis showed that post-transcriptional regulation has a large impact on the expression of functional proteins during xylem vessel cell differentiation.…”
Section: Resultsmentioning
confidence: 61%
“…Recent comparative studies between proteomic and transcriptomic data revealed low correlations for a certain number of genes (Cheng et al 2016;Liu and Aebersold 2016;Peng et al 2015;Vogel and Marcotte 2012). The expression of functional proteins is tightly regulated at the post-transcriptional level, including translational regulation and post-translational modification (Cheng et al 2016;Liu and Aebersold 2016;Peng et al 2015;Vogel and Marcotte 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, generally there is only a limited degree of correlation between the levels of mRNAs and their encoded proteins (14), emphasizing the significant effect of post-transcriptional regulation on protein levels.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various large scale techniques for estimating variables related to mRNA translation have been developed (1,34,2441). Thus, in the recent and following years computational models of translation on the basis of high-throughput, genome-wide datasets, are expected to be instrumental in deciphering this process (12,7,12,19,4270).…”
Section: Introductionmentioning
confidence: 99%
“…When translation rate constants are included the correlation is much stronger, which suggests that the rate of translation, and not necessarily the overall levels of mRNA in a cell, may be a dominant process that controls protein expression 6 . However, this view has recently been challenged by the observation that the kinetics of both synthesis and degradation of RNA and protein are equally involved in regulating cellular homeostasis in response to an acute stressor 7 . Jovanovic et al 8 note that RNA abundance contributes significantly to protein levels at steady state in immune cells and that this relationship is even more pronounced following stimulation, in accordance with the idea that translation and degradation might predominate, although in a context-specific manner 9 .…”
mentioning
confidence: 99%